Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.14260/jemds/2018/323
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Given as Iv Bolus Versus Iv Infusion in Women Undergoing Caesarean Sectiona Randomised, Controlled, Double-Blind Study

Abstract: BACKGROUNDOxytocin is the uterotonic of choice in the prevention of uterine atony. It reduces blood loss during both vaginal deliveries (1) and caesarean sections. Its prophylactic and therapeutic administration is justified, because it is said to reduce the incidence of PPH by about 40%. However, bolus use of oxytocin is known to cause cardiovascular effects including tachycardia, hypotension and ST changes. Aims and Objectives-To compare the uterine tone, blood loss and haemodynamic responses on intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Studies conducted with the use of 5 IU have shown significant hemodynamic changes. 20 However, doses of 3 IU have not shown to cause statistically significant hemodynamic changes. 4 Various studies have used higher doses of Oxytocin infusion of 40 IU.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted with the use of 5 IU have shown significant hemodynamic changes. 20 However, doses of 3 IU have not shown to cause statistically significant hemodynamic changes. 4 Various studies have used higher doses of Oxytocin infusion of 40 IU.…”
Section: Discussionmentioning
confidence: 99%
“…The IV bolus dose of oxytocin is quicker in action in comparison to the IM route. The applied dose of IV bolus oxytocin in cesarean section (C-section) has been variable, including 10, 5, 3, 2, and 1 IU of IV oxytocin bolus (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%